PSYCHOLOGICAL AND PEDAGOGICAL FEATURES OF TEACHING ADULTS TO PLAY THE PIANO (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Teaching adults to play the piano requires a fundamentally different psychological, pedagogical, and methodological approach compared to teaching children. Adult learners possess developed cognitive abilities, stable motivation, and clear goals; however, they also face specific challenges such as limited motor plasticity, time constraints, performance anxiety, and pre-existing beliefs about their abilities. This study examines the psychological mechanisms underlying adult musical learning, identifies pedagogical strategies that optimize piano instruction for adults, and evaluates the effectiveness of modern teaching approaches. The article follows the IMRAD structure and integrates theoretical literature, observational data, comparative analysis, and a sample diagram illustrating differences between adult and child learning characteristics. The results show that personalized instruction, cognitive-based strategies, emotional support, and flexible pacing significantly contribute to adults’ success in piano performance. The discussion highlights the importance of motivation, neuroplasticity, self-regulated learning, and teacher empathy in adult piano pedagogy.